The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/petr.13004
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation in pediatric patients with acute myeloid leukemia without favorable cytogenetics

Abstract: Intensified chemotherapy, HSCT, and supportive care improve the survival of pediatric patients with AML. However, no consensus has been reached regarding the role of HSCT in patients without favorable cytogenetics. We evaluated OS and EFS according to prognostic factors that affect clinical outcomes, including cytogenetics risk group, conditioning regimen, donor type, disease status at the time of HSCT, and number of chemotherapy cycles prior to HSCT in 65 pediatric patients with AML without favorable cytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…Over 70% of children with HR AML who received allo‐HSCT immediately after obtaining CR1 survived. We observed that the cumulative incidence rates of NRM and aGVHD/cGVHD were also similar to those reported in previous studies . This further supports the safety of this technique despite the fact that 74% of grafts were from alternative donors.…”
Section: Discussionsupporting
confidence: 90%
“…Over 70% of children with HR AML who received allo‐HSCT immediately after obtaining CR1 survived. We observed that the cumulative incidence rates of NRM and aGVHD/cGVHD were also similar to those reported in previous studies . This further supports the safety of this technique despite the fact that 74% of grafts were from alternative donors.…”
Section: Discussionsupporting
confidence: 90%
“…In the AML cases, the detailed informations about regimen for chemotherapeutic protocols and allogeneic haematopoietic cell transplantation used in our study are represented in the previous literatures. 14,15 The clinical and laboratory characteristics of these patients are summarized in Table 1.…”
Section: Bone Marrow Specimens and Study Populationsmentioning
confidence: 99%
“…Remarkable improvements have been made in the field of HSCT in children and adolescents over the last decade because of the development of optimal conditioning regimens, more effective graft-versus-host disease (GVHD) prophylaxis, and advancements in post-transplant care. In an experienced transplant center, patients who received HSCT from a matched unrelated donor (URD) showed similar outcomes to those who received HSCT from a human leukocyte antigen (HLA)-matched sibling donor (MSD) [ 7 8 ]. Furthermore, the outcomes of HSCT even with an alternative donor, including transplants using umbilical cord blood or a haploidentical family donor, significantly improved [ 9 10 ].…”
mentioning
confidence: 99%